Penerapan Kinerja Mashlahah Performa dalam Penghimpunan Harta di Al Muttaqin Kota Tasikmalaya (Implementation of Mashlahah Performance in Asset Collection in Al Muttaqin, Tasikmalaya City) - Rohman, Pupun Saepul; Ramdani, Ramdani; Krisnaningsih, Diah (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to examine the management of assets at the Al Muttaqin Foundation LPI for its suitability with maqāṣid syarīah in its measurement using Maslahah Performance (MaP) developed by Ahmad Firdaus (2014). Research related to educational institutions' performance was conducted by Arianti (2014) on the implementation of financial management in private educational institutions. Another study was conducted by Gunanta (2012) using the Balanced Scorecard concept and Firdaus and Prianto (2012) using the Maslahah Scorecard concept. This study's results indicate that, in general, LPI Al Muttaqin has fulfilled asset collection performance based on maqaṣid sharia. This is evidenced by the scores of the six Maṣlahah Performance orientations (MaPs), which are greater than the threshold score for the assessment criteria.